Meningkatkan Kemampuan Menulis Kata Beraksara Bali Menggunakan Media Balok Aksara Bali Siswa Kelas IV SD Negeri 1 Galungan: Improving the Ability to Write Balinese Script Words Using Balinese Script Blocks Media for Fourth Grade Students of SD Negeri 1 Galungan - Maharani, Ni Putu Andina Putri; Wirani, Ida Ayu Sukma; Paramarta, I Ketut (Universitas Tidar, 2025)
Learning Balinese script in elementary schools still faces obstacles, especially in student understanding. The lack of innovative and interactive learning media causes students to have difficulty recognizing and writing Balinese script, which has an impact on their low interest in learning. Therefore, innovation is needed in learning media, one of which is the Balinese script block media, which is designed to improve Balinese script writing skills systematically and attractively. The subjects of this study were at SD Negeri 1 Galungan, grade IV students with a total of 23 students. The object of the study was the Balinese script block media as a means to improve the ability to write Balinese script words. The methods used were descriptive qualitative and quantitative, with data collected through observation, tests, and questionnaires. The success of the study was analyzed using normality tests, homogeneity tests, and hypothesis testing to ensure the validity of the results. The research findings showed that: (1) Balinese script block media was applied through the planning, implementation, and evaluation stages, which helped students understand the form and use of Balinese script more effectively. (2) The test results showed an increase in Balinese script writing skills, with an average score of 80.04 in cycle I, increasing to 85.61 in cycle II. (3) Students' responses to this media also increased, from a good category (19.91) in cycle I to 24.48 in cycle II, indicating higher enthusiasm in learning. The use of Balinese script block media has proven effective in improving Balinese script writing skills and creating a more interactive and enjoyable learning experience. This media not only helps students understand the form and rules of Balinese script, but also increases their involvement in learning. Therefore, this media is recommended as an alternative in learning Balinese script in elementary schools to support the preservation of Balinese script. The implications of this study indicate that interactive-based learning media innovations can be applied in formal and non-formal education systems to expand access to Balinese script learning.